Medicine science and dreams the making of physician-scientists - Schwartz, David A. (Dordrecht, Netherlands Springer, 2011)
Physician-scientists are unusual creatures. While we are drawn to the clinical challenges of our patients, we are also drawn to the opportunities that our patients' medical problems bring to science. This book contains the unique experiences and encounters that drew 21 accomplished physician-scientists to this profession. These personal stories are those of people and circumstances that have had profound effects on our career decisions, our creative opportunities, and our lives. These stories also serve to highlight the lessons learned along the way and the distinct attributes of these women and men of medicine and science. Our combined hope is that our collective biographies will enhance the public understanding of our profession, will move people from medicine to science and from science to medicine, and will inspire those who are contemplating this extraordinary profession.
1. The Loneliness of the Physician-Scientist - Fernando D. Martinez -- 2. Gamow, Guppies, and the Search for GOD - David S. Pisetsky -- 3. The Epigenesis of an Epigeneticist - Andrew P. Feinberg, MD, MPH -- 4. A Delicate Balance: Science, Medicine, and Motherhood - Laurie H. Glimcher -- 5. First Pick Good Parents - Edward J. Benz, Jr -- 6. The Long Way to Somewhere - Moisés Selman -- 7. Sputnik, Slime Molds, and Botticelli in the Making of a Physician-Scientist - R. Sanders Williams -- 8. Success for the Whole Community---Play to Win - Talmadge E. King, Jr -- 9. The Irony of Disease - David A. Schwartz -- 10. Serendipity and Stamina: Staying the Course - Barton F. Haynes -- 11. Twists and Turns on the Road to Becoming a Physician-Scientist - Stephen I. Katz -- 12. Journeys from Bedside to Bench and Back - Jeffrey C. Murray -- 13. Life Comes to One - Erika von Mutius -- 14. What is a Guy Like You Doing in a Place Like This? A Physician-Scientist in the Private Sector - Gilad S. Gordon -- 15. The Jock and the Doc - Michael D. Iseman -- 16. The Making of a Medical Epidemiologist - Philip J. Landrigan -- 17. Curiosity, Hard Work, and Tenacity - Moira Chan-Yeung -- 18. Physician-Scientist: Linking Science, Medicine, and Public Policy - Gilbert S. Omenn -- 19. Pursuit of a Patient-Oriented Research Career as a Physician-Scientist - Robert W. Schrier -- 20. What Went Right - Ralph I. Horwitz.
Electronic reproduction.
Keywords: Medicine -- Vocational guidance; Medical Scientist -- Biography; Physicians -- Biography; Electronic books; Electronic books